Internal and External Checks in the Nosams Sample Preparation Laboratory for Target Quality and Homogeneity - Osborne, E. A.; McNichol, A. P.; Gagnon, A. R.; Hutton, D. L.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
In the NOSAMS sample preparation laboratory (SPL) we have developed rigorous internal procedures aimed at ensuring that sample preparation introduces as little error into our analyses as possible and identifying problems rapidly. Our three major CO2 preparation procedures are: stripping inorganic carbon from seawater, hydrolyzing CaCO3, and oxidizing organic matter. For seawater, approximately 10% of our analyses are standards or blanks which we use to demonstrate extraction of virtually all the inorganic carbon. Analysis of the stable carbon isotopic composition of the CO2 extracted from our standards indicates a precision of better than 0.15-0.20 parts per thousand. We also routinely process C-14-free CO2 in our stripping lines to demonstrate the absence of a significant process-dependent blank. For organic combustions and CaCO3 hydrolyses, we use the carbon yield (% organic carbon (OC) or % CaCO3 by weight) as a check on our sample procedures. We have analyzed the blank contribution of these procedures as a function of sample size. Our organic carbon blank is constant at approximately 0.4% modem for samples containing greater than 1 mg C and our carbonate blank is less than 0.2% modern for samples containing more than 0.5 mg C. We use a standard Fe/H-2 catalytic reduction to prepare graphite from CO2. We check the completeness of our reactions with the pressure data stored during the reaction as well as use a robot to determine a gravimetric yield. All graphite undergoes a visual inspection and is rejected if any heterogeneities are present. We have recombusted graphite made from CO2 with deltaC-13 values ranging from -42 to 1 parts per thousand and determined that the deltaC-13 of the recombusted carbon agrees with that from the pure gas to within 0.05 parts per thousand, demonstrating little or no fractionation during the treatment of the sample. The deltaC-13 we measure on the CO2 generated from more than 75% of our samples is compared to the deltaC-13 measured on the AMS as a further check of our procedures. As further external checks, we analyzed the International Atomic Energy Association (IAEA) samples during the establishment of our laboratory and are presently participating in the third international radiocarbon intercalibration (TIRI) exercise.
Nv547Times Cited:14Cited References Count:5